Pharmacokinetic Interaction of Paeoniflorin and Sinomenine: Pharmacokinetic Parameters and Tissue Distribution Characteristics in Rats and Protein Binding Ability In Vitro - Zhong Qiu Liu; Zhi Hong Jiang; Kelvin Chan; Hua Zhou; Yuen Fan Wong; Zhao Xiang Bian; Hong Xi Xu; Liang Liu (Elsevier, 2005)
The root of Paeonia lactiflora and the stem of Sinomenium acutum are two herbs widely used in Chinese herbal medicine for the treatment of inflammatory and arthritic diseases. Studies on the interaction of the active constituents of these herbs, i.e., paeoniflorin and sinomenine, in pharmacokinetic parameters, tissues distribution, and protein binding ability could provide empirical data to support their clinical application. Following oral administration to rats, the pharmacokinetic alterations were compared. The results showed that the pharmacokinetic parameters (Cmax, Tmax, AUC, MRT, CL, and Vd) of paeoniflorin were markedly enhanced when co-administrated with sinomenine. At 45 min after oral administration, the concentrations of paeoniflorin in the main internal organs were significantly increased when co-administrated with sinomenine. These phenomena were not ascribable to the alteration of the protein binding ability of paeoniflorin by sinomenine because obvious interactions of paeoniflorin and sinomenine in protein binding abilities in vitro to rat and rabbit plasma, human albumin, and α-1-acid-glycoprotein were not observed. However, with respect to the in vivo influence of paeoniflorin on sinomenine, the results showed that co-administration of paeoniflorin did not affect the pharmacokinetic parameters and tissue distribution of sinomenine. Keywords:: paeoniflorin, sinomenine, pharmacokinetics, bioavailability, tissue distribution